A consciência fonológica no processo de alfabetização: análise do curso de formação continuada em práticas de alfabetização - Araújo, Rosivânia Diniz (2022)
The purpose of literacy is that children understand the reading and writing system, autonomously and continuously. Recent researches in this area have been emphasizing the importance of metalinguistic skills to promote success in the initial learning of reading and writing: literacy, mainly related to the ability of phonological awareness. The research has a qualitative approach in the exploratory modality, as it allows for a deeper understanding of the problem under study, as well as improving information that will support the construction of concepts and hypotheses, enabling more promising conclusions and results for the research. The present study aims to discuss the approach aimed at working with Phonological Awareness in the literacy process, based on the analysis of module 02 of the Continuing Education in Literacy Practices course. As specific objectives, we intend to: (i) analyze the methodologies proposed for working with phonological awareness; (ii) analyze the resources adopted; (iii) understand the concept of literacy that permeates the course. To carry out the objectives, we took as a basis the theoretical reflection of authors such as Magda Soares ( 2003, 2004, 2014, 2020); Morais (2012, 2021) Capovilla (2004); Adams (2006); Almeida (2003); Kleiman (1995); Blacksmith (1996); Kato (1994), Pessoa (2007), Mortatti (2008, 2006, 2014) and also in official documents that guide education. In addition to the bibliographic research, for the generation of data, a critical analysis of the Continuing Training in Literacy Practices course will be carried out, offered by the Ministry of Education, online, through the AVAMEC platform - Tempo to learn, with the partnership of 23 institutions. The course “Literacy Practices” was emphatically authoritarian, reductionist and retrograde, imposing the phonic method as a solution and better induction to the literacy process, based on scientific evidence and experimental studies, disregarding the entire history of Brazilian literacy. We can conclude that the development of the Phonological Awareness skill can be a relevant factor in the literacy process, but as long as the conduction to this literacy is broad, debatable, diversified and not reduced to just this or that method, but that the field of opportunity for students.